Sustainable food crop production through multiple cropping patterns among farmers in South Western Nigeria (2007)
This paper examined the medley of food crops among farmers as a method of evolved sustainable food crop production. Farmers from different groups were randomly selected and a structured questionnaire was administered on them to elicit information in the areas of crop mixtures and reasons for such mixtures. The result of the study indicates farmers profile with a mean age of 53.4 years with majority married (78%), having non-formal education (37%) and long years of farming experience (39%). Yam maize crop mixture was the most prominent among farmers and the assurance of food security was the prevailing reason for multiple cropping. The study has thus, provided clear insight into the practice of multiple cropping by farmers in the study area and also a basis for a demand-led technology development for the improvement of production.